A contribuição do macromarketing para o ensino de marketing no Brasil - Berardinelli, Rodolfo Peres (2017)
It addresses the teaching of marketing and the role of themes belonging to macromarketing in Brazil. It highlights how the marketer is seen in the market and in society. It presents the role of macromarketing as a connector of the different management themes. It shows the importance of macromarketing to be a course of administration course, which will have as content the history of marketing to clarify the division of mircomarketing and macromarketing; the functioning of marketing systems; the relevance of social marketing and the impact of marketing on society.